2022
DOI: 10.3390/molecules27030738
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin as a Senotherapeutic Agent: Biopharmaceutical Properties and Crosstalk between Cell Senescence and Neuroprotection

Abstract: Like other organs, brain functions diminish with age. Furthermore, for a variety of neurological disorders—including Alzheimer’s disease—age is one of the higher-risk factors. Since in many Western countries the average age is increasing, determining approaches for decreasing the effects of aging on brain function is taking on a new urgency. Neuroinflammation and oxidative stress are two convoluted key factors in brain aging and chronic neurodegenerative diseases. The diverseness of factors, causing an age-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 99 publications
0
21
0
1
Order By: Relevance
“…Different mechanisms of action of senolytics have been reported in the literature: inhibition of the BCL-2 antiapoptotic family, negative modulation of the PI3K/Akt pathway and FOXO regulation [ 28 ]. On the other hand, senomorphics revert or slow down senescence by regulating the SASP [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different mechanisms of action of senolytics have been reported in the literature: inhibition of the BCL-2 antiapoptotic family, negative modulation of the PI3K/Akt pathway and FOXO regulation [ 28 ]. On the other hand, senomorphics revert or slow down senescence by regulating the SASP [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although all senolytic drugs appear to clear senescent cells, each drug’s exact roles and mechanisms, especially in different contexts in vivo, still are unclear. 52 , 53 Even though it has been reported that D+Q showed selective cytotoxicity toward senescent HSCs, 26 the study mentioned earlier indicated that fisetin selectively eliminated senescent cholangiocytes, whereas D+Q targeted both proliferating and senescent cholangiocytes. 48 Furthermore, we performed senolytic administration ahead of CCl 4 injection to ensure the depletion of senescent HSCs in the present study, whereas the report mentioned earlier only focused on the senescent cholangiocytes.…”
Section: Discussionmentioning
confidence: 99%
“…SCAPs can be targeted by small molecule senolytic compounds to selectively clear senescent cells from pathological tissues 125 . Fisetin, a natural flavonoid, has senolytic properties and can be added to the diet as a supplement with minimal adverse effects 126 . We fed Ts65Dn mice a diet supplemented with 500ppm Fisetin, as previously described 127 (Methods).…”
Section: Treatment With the Senescence-reducing Flavonoid Fisetin Res...mentioning
confidence: 99%